Augmented Reality-Supported Reading Instruction: Fostering Reading Literacy and Critical Thinking in Primary Schools - Febrina Dafit; Khairil Ansari; Yusnadi Yusnadi (CV FOUNDAE, 2026)
The fast-paced development in information technology has resulted in a change i The increasing integration of digital technologies into primary education has created new opportunities to strengthen literacy instruction, yet empirical evidence on how augmented reality (AR) supports both reading literacy and critical thinking among young learners remains limited. This study investigated the effectiveness of AR-supported reading instruction in enhancing primary school students’ reading literacy and critical thinking while exploring their learning experiences in technology-enhanced classrooms. An explanatory sequential mixed-methods design was employed involving 147 fifth-grade students from two primary schools in Pekanbaru, Indonesia. Quantitative data were collected through pre- and post-intervention assessments, followed by semi-structured interviews with selected students and teachers to explain the observed learning outcomes. The findings indicate that AR-supported instruction substantially improved students’ reading literacy and critical thinking compared with conventional classroom learning. Qualitative evidence further revealed that interactive three-dimensional visualizations, collaborative learning activities, and teacher-guided questioning promoted deeper text comprehension, active participation, and analytical reasoning throughout the learning process. This study extends current research by demonstrating that the educational value of augmented reality lies not only in its technological features but also in its capacity to facilitate meaningful instructional interactions that support higher-order cognitive development. The findings provide practical guidance for integrating augmented reality into primary literacy instruction to foster students’ reading literacy and critical thinking in digitally enriched learning environments.